Answer:
1) y = (x + 8)² + 7; 5) y = (x - 6)² + 10; 7) y = (x - 3)² - 4
Step-by-step explanation:
Complete the square in order to figure these out. To complete the square, use the formula <em>[½B]</em><em>²</em><em>.</em><em> </em>Each time you do this, you get a perfect trinomial in the form of a product of two monomials [<em>h</em>], then you have to figure out how much more to deduct from or add on to your <em>C</em><em> </em>they gave you in each exercise [<em>k</em>].
If you are still in need of assistance, do not hesitate to let me know and subscribe to my channel [username: MATHEMATICS WIZARD].
I am joyous to assist you anytime.
Answer:
- 25 and - 623
Step-by-step explanation:
Using the term to term rule with u₀ = - 3 , then
(a)
u₁ = u₀³ + 2 = (- 3)³ + 2 = - 27 + 2 = - 25
(b)
u₂ = u₁³ + 2 = (- 25)³ + 2 = - 625 + 2 = - 623
Answer:
https://youtu.be/AWGqoCNbsvM
Step-by-step explanation:
okay?
Answer:
sorry I don't no the answer